56=-1+3x

Simple and best practice solution for 56=-1+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56=-1+3x equation:


Simplifying
56 = -1 + 3x

Solving
56 = -1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
56 + -3x = -1 + 3x + -3x

Combine like terms: 3x + -3x = 0
56 + -3x = -1 + 0
56 + -3x = -1

Add '-56' to each side of the equation.
56 + -56 + -3x = -1 + -56

Combine like terms: 56 + -56 = 0
0 + -3x = -1 + -56
-3x = -1 + -56

Combine like terms: -1 + -56 = -57
-3x = -57

Divide each side by '-3'.
x = 19

Simplifying
x = 19

See similar equations:

| 7(2a-8)+6=-92 | | 5-9a-14/3(2a) | | Z=-5z | | 2x^3-4x^2= | | 2l+6=6-10 | | Y-2+3x=6+5x | | 1/2x-y=3 | | 4x-(2x-10)=2x-6 | | sqrtx+2=3 | | 12x+10=14x | | -5(3-q)+4=5q | | 5(b+1)-6=2b-16 | | 8.364km= | | 1/3=4/6q | | 2y+3(0)y=10-0 | | 6m-2=-2-7m-m | | 15(x-3)=105 | | 3/4-3/4=0 | | -8(-2b+2)=-128 | | -8(1-4p)=120 | | 6t+3(5+-4)=12(2+-5) | | 6+2(33-x)-3+x= | | (25x)/45=-67 | | 2(5x-6)-3(1-x)=4-6(x+2) | | 5/7÷1/3 | | 12-3(4w-1)=7w-3(7+w) | | 2x+7-3x=6x-1 | | 6-2x-1=4x+6-6x-3 | | -(5b-1)=5b-(b-4) | | 7y^2-68y-20=0 | | -5-3(1-8p)=18-2p | | 2y-3x(x-8)=0 |

Equations solver categories